2017
DOI: 10.1016/j.anihpc.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-degenerate elliptic operators and Hölder continuity for solutions to variational equations and inequalities

Abstract: Abstract. We prove local supremum bounds, a Harnack inequality, Hölder continuity up to the boundary, and a strong maximum principle for solutions to a variational equation defined by an elliptic operator which becomes degenerate along a portion of the domain boundary and where no boundary condition is prescribed, regardless of the sign of the Fichera function. In addition, we prove Hölder continuity up to the boundary for solutions to variational inequalities defined by this boundary-degenerate elliptic opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…However, the proof of even the weak maximum principle for a weakly A-subharmonic function in W 1,2 (O) is neither as direct nor as intuitive as that presented here, since it relies on a certain weighted Sobolev inequality (see [19,Theorem 8.8]). Moreover, an analogue of the classical proof of the strong maximum principle (see [27,Theorem 8.19]) would require an analogue of the classical weak Harnack inequality (see [27,Theorem 8.18]) valid for the boundary-degenerate elliptic operator, A, written in divergence form (see [20,Theorem 1.23] for such a result in the case of the Heston operator [30]). The proof of our Harnack inequality for the boundary-degenerate elliptic Heston operator, developed with C. Pop, is lengthy and difficult, relying on a Moser iteration argument, the abstract John-Nirenberg inequality due to Bombieri and Giusti [4,Theorem 4], Poincaré and Sobolev inequalities for weighted Sobolev spaces [20, §2], and delicate choices of test functions.…”
Section: 3mentioning
confidence: 99%
“…However, the proof of even the weak maximum principle for a weakly A-subharmonic function in W 1,2 (O) is neither as direct nor as intuitive as that presented here, since it relies on a certain weighted Sobolev inequality (see [19,Theorem 8.8]). Moreover, an analogue of the classical proof of the strong maximum principle (see [27,Theorem 8.19]) would require an analogue of the classical weak Harnack inequality (see [27,Theorem 8.18]) valid for the boundary-degenerate elliptic operator, A, written in divergence form (see [20,Theorem 1.23] for such a result in the case of the Heston operator [30]). The proof of our Harnack inequality for the boundary-degenerate elliptic Heston operator, developed with C. Pop, is lengthy and difficult, relying on a Moser iteration argument, the abstract John-Nirenberg inequality due to Bombieri and Giusti [4,Theorem 4], Poincaré and Sobolev inequalities for weighted Sobolev spaces [20, §2], and delicate choices of test functions.…”
Section: 3mentioning
confidence: 99%
“…In [11] it is shown that this natural boundary condition can be understood as imposing a regularity requirement along these boundary components. Similar problems without boundary conditions on suitable portions of the boundary have been studied in [8,34,21,20,22,19], among others.…”
Section: Remark 23 (Boundary Condition Alongmentioning
confidence: 99%
“…, such that for all 4r 2 < t < T − 4r 2 and for all p ∈ ∂P we have that sup Finally, we remark that the class of processes described by generalized Kimura operators appear not only in population genetics, but they are also encountered in the study of superprocesses, [1,2], of Fleming-Viot processes in population dynamics, [3,4,5,6], and are closely related to the linearization of the porous medium equation, [8,34], to affine models for interest rates, [7,10], and to stochastic volatility models in mathematical finance, [31,20,21,22,23,24,25].…”
Section: Theorem 12 (Boundary Regularity)mentioning
confidence: 99%
“…However, in this setting, the boundary condition is not mixed, since there is no Dirichlet condition along any portion of ∂O, only the condition (1.8) implied by the regularity of u up to ∂O. By extending the methods of Koch [26] and restricting to the case where A is the Heston operator (1.24) and d = 2, Daskalopoulos, Pop, and the author succeeded in proving existence, uniqueness, and regularity os solutions to the equation (1.1) and obstacle problem (1.3) with partial Dirichlet boundary condition (1.2) by solving the associated variational equation and inequality for solutions, u, in weighted Sobolev spaces [8]; appealing to [13] to obtain uniqueness; proving that the solutions are continuous up to the boundary [15] using a Moser iteration technique; proving Schauder regularity when f ∈ C ∞ 0 (O) ∩ C b (O) using a variational method [16]; proving the expected Schauder regularity, u ∈ C 2+α…”
mentioning
confidence: 99%
“…However, the Perron methods which we use in this article, and which we outline in §1.7, provide a more direct and elegant path to the desired results, even though they do not establish continuity of the solution at the corner points, although such continuity properties are proved by Pop and the author by a variational method in [15] for the case of the Heston operator (1.24). It is important to note that the Perron methods developed in this article are analogues of their classical counterpart in [20,Chapters 2 and 6] for the existence of smooth solutions to a Dirichlet problem for a linear, second-order, strictly elliptic operator.…”
mentioning
confidence: 99%